Removing Malachite Green and Leucomalachite Green From Freshwater and Seawater With Four Water Treatment Agents - Lin, Yu-Ru; Hu, Yeh-Fang; Huang, Chih-Yang; Huang, Huai-Ting; Liao, Zhen-Hao; Lee, An-Ting; Wu, Yu-Sheng; Nan, Fan-Hua (Frontiers in Environmental Science, 2022)
Malachite green (MG) residue in aquatic environments can adversely affect food chains. Many adsorbents have been developed to remove MG from aqueous solutions, and these adsorbents exhibit benefits such as low cost, nontoxicity, and environment friendliness. Zeolite, oyster shell powder, humic acid, and ClO2 are widely used agents for water purification, indicating their potential to remove MG from both freshwater and seawater. Liquid chromatography tandem mass spectrometry was performed as a valid analytical method for measuring MG and its metabolite leucomalachite green (LMG). The analysis examined linearity, specificity, accuracy, precision, and limit of quantification. We found that three agents—zeolite, oyster shell powder, and humic acid—have high affinity for MG and LMG in both freshwater and seawater because of their physicochemical properties; ClO2 exhibited even greater efficiency for MG and LMG degradation because of its oxidation capacity. In this study, these four water treatment agents removed MG and LMG from freshwater and seawater, indicating their potential for reducing the amount of hazardous MG and LMG residue in aquatic environments.